La nozione di magia nell'immaginario antico - Cioccoloni, Alessandra (Euphrosyne, 2004)
Abstract The following essay is an attempt to demonstrate the connection between two typical features of the ancient magic: its female and foreigner nature. These features are implied within the concept of «non - omnipotence», which is connected with the idea of dolus (stemmed from the ancient magic) and in opposition to the divine omnipotence.